Implementasi Algoritma Probabilistic Symmetric Untuk Mendiagnosa Penyakit Karies Gigi Pada Anak-Anak (Studi Kasus Klinik Sehati Bengkulu) - Pratama, Ropi Devin Agustian; Jumadi, Juju; Zulfiandry , Ricky (CV. Generasi Insan Rafflesia, 2023)
Cavities or caries are conditions that are very common and experienced by anyone, especially children who are susceptible to them. The condition of dental caries in children may one day have an impact when the children are adults. However, many people are unfamiliar with dental caries, so a system that can be accessed online is needed to help patients or the public to consult independently. This expert system uses the Probabilistic Symmetric method using the PHP programming language and MySQL database. The resulting expert system can make it easy for users to make early diagnoses of dental caries online.